Work system barriers and facilitators in inpatient care transitions of pediatric trauma patients. (May 2020) - Wooldridge, Abigail R.; Carayon, Pascale; Hoonakker, Peter; Hose, Bat-Zion; Eithun, Benjamin; Brazelton, Thomas; Ross, Joshua; Kohler, Jonathan E.; Kelly, Michelle M.; Dean, Shannon M.; Rusy, Deborah; Gurses, Ayse P.
Abstract: Hospital-based care of pediatric trauma patients includes transitions between units that are critical for quality of care and patient safety. Using a macroergonomics approach, we identify work system barriers and facilitators in care transitions. We interviewed eighteen healthcare professionals involved in transitions from emergency department (ED) to operating room (OR), OR to pediatric intensive care unit (PICU) and ED to PICU. We applied the Systems Engineering Initiative for Patient Safety (SEIPS) process modeling method and identified nine dimensions of barriers and facilitators – anticipation, ED decision making, interacting with family, physical environment, role ambiguity, staffing/resources, team cognition, technology and characteristic of trauma care. For example, handoffs involving all healthcare professionals in the OR to PICU transition created a shared understanding of the patient, but sometimes included distractions. Understanding barriers and facilitators can guide future improvements, e.g., designing a team display to support team cognition of healthcare professionals in the care transitions. Highlights: Work system barriers and facilitators influence care transitions of pediatric trauma patients. Team cognition is an important dimension of barriers and facilitators in care transitions. Future solutions should support all members of the care team during care transitions.